Multiwavelength Emission of Gamma-Ray Burst Prompt Phase. II. Spectral Polarimetry - Jia-Sheng Li; Mi-Xiang Lan (The Astrophysical Journal)
Polarization spectra were predicted within the photosphere model. To seek more clues to distinguish between the models, both the time-resolved and time-integrated polarization spectra from optical band to MeV gamma-rays of the magnetic reconnection model are studied here. There are two newly found differences between the two models. First, the time-integrated polarization degree of the magnetic reconnection model would in general increase with frequency for on-axis observations, while it is not monotonous for the photosphere model. Second, the variations of both the time-integrated and the time-resolved polarization angles (PAs) with frequency of the magnetic reconnection model are not random, while the time-integrated PA varies randomly with frequency for the photosphere model. Therefore, future energy-resolved polarization analysis could distinguish between the two models. In addition, the PA rotation spectra are studied for the first time. The rotation value of PA within the burst duration will decrease with the increase of the observational energy band. Most significant PA rotation would happen for slightly off-axis observations in each energy band. The PA would rotate even for on-axis observations in the optical band. Compared with the aligned magnetic field case, the PA rotation is quite rare in the gamma-ray band for the case with a toroidal field in the radiation region.